Quality of life in the educational inclusion of children and adolescents with intellectual disabilities. (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2019)
ABSTRACTINTRODUCTION: The objective is to determine the relationship between the quality of life of chil-dren and adolescents with intellectual disabilities in an educational institution and a rehabilitation center in a neighborhood of the city of Cúcuta, through the KidsLife scale, and in this way answer the research question. METHODS: Corresponds to a quantitative study of correlational type, cross-sec-tional whose sample consisted of 24 subjects of an educational institution and a rehabilitation center. RESULTS: Significant differences were found in the fiscal welfare dimension with a score of 12 for out-of-school children and 8.5 for school-age children. At the general level, no significant differences were found in the quality profile, educational inclusion scored a score of 9.667 and the other collective of 9.25. ANALYSIS AND DISCUSSION: The quality of life is given by a multidimensional model that is related to both personal and environmental factors. CONCLUSIONS:When evaluating the quality of life, the different contexts in which the individual develops should be taken into account.
Keywords: Quality of Life; Intellectual Disability; Child; Adolescent